Histological Characteristics of Intracranial Atherosclerosis in a Chinese Population: A Postmortem Study - Yang, Wen Jie; Fisher, Mark; Zheng, Lu; Niu, Chun Bo; Paganini-Hill, Annlia; Zhao, Hai Lu; Xu, Yun; Wong, Ka Sing; Ng, Ho Keung; Chen, Xiang Yan (Frontiers in Neurology, 2017)
Background: Anterior and posterior circulation atherosclerosis differ in vascular risk factors and stroke mechanisms. However, few studies have compared the pathological features between these lesions. Using a series of intracranial artery specimens, we characterized the intracranial atherosclerotic lesions and compared pathological features among different arteries of the intracranial vasculature. Methods: Intracranial large arteries of 32 consecutively recruited autopsy cases of Chinese adults aged 45 years or older were examined pathologically using routine histology and immunostaining, to characterize the pathological features of the atherosclerotic lesions. We analyzed middle cerebral arteries (MCA) (both left and right), vertebral arteries (VA) (side more affected) and basilar arteries (BA). Results: Progressive atherosclerotic lesions were present in 91(71%) of the 128 arteries examined. Features of complicated plaques were infrequently detected: plaque hemorrhage was encountered in 12%, neovasculature in 12%, lumen thrombi in 13%, macrophage infiltration in 20%, and calcification in 25% of arteries. Luminal narrowing of MCA was the most severe, followed by VA; the BA least stenotic (37±25% vs. 30±24% vs. 20±20%, all p<0.05). MCA had more eccentric (versus concentric) plaques than VA (69% vs. 25%, p=0.003) and BA (69% vs. 38%; p=0.03). Lumen thrombi were more frequent in BA, and calcification most commonly occurred in VA atherosclerotic lesions. Conclusions: Intracranial atherosclerotic plaques were commonly present in this sample, but the lesions generally lacked features of complicated plaques. MCA lesions had demonstrable differences compared with VA and BA lesions. Further studies are needed to determine whether these characteristics indicate a distinctive atherosclerotic phenotype for the intracranial vasculature.